Validating Fibula Length as a Reliable Estimator for Femoral Nail Length: A Comparative Analysis with the Standard AO Method - Ab Rahman, Shaifuzain; Sandhu, Manharpreet Singh; Sharifudin, Mohd Ariff; Ismail, Ahmad Filza (IIUM Medical Journal Malaysia, 2025)
INTRODUCTION: An appropriate femoral nail length is required to be measured preoperatively to ensure optimal surgical outcomes. Conventionally, measurements are obtained clinically or radiographically on the contralateral femur or by using forearm referencing. This study is aimed to determine whether fibula length can be used as an additional clinical method for estimating maximum femoral nail length. MATERIALS AND METHOD: This study involves measuring the femurs and fibulas of 140 patients using a standard tape measure. Femur length is measured adhering to the standard Arbeitsgemeinschaft für Osteosynthesefragen (AO) method, while fibula length was measured from the tip of the fibula head to the tip of the lateral malleolus. Pearson correlation coefficient (r) determines any correlation between the two measurements. RESULTS: The overall mean femoral length was 37.98cm (SD=2.72), with a range of 32.0 to 46.5 cm, and the mean fibula length was 37.72cm (SD=2.61), with a range of 32.4 to 47.0 cm. A robust and positive correlation (r=0.940, p<0.001) was observed between fibula length and femoral length. Age, body mass index, and gender did not affect this correlation. Both inter-observer and intra-observer reliabilities were high. A formula for estimating maximum femoral nail length was derived from the correlation graph: femoral nail length = 1 + (0.98 x fibula length). CONCLUSION: Fibula length demonstrates a strong correlation with femoral length, offering a reliable alternative clinical method for estimating femoral nail length. This method proves particularly useful in cases of bilateral femoral fractures with concurrent forearm fractures where forearm referencing method is impractical.